A STUDY ON THE SAFETY AND EFFICACY OF MONOGLYCERIDE OF LAURIC ACID AS ADJUVANT TREATMENT IN PERSONS LIVING WITH HIV INFECTION - Eric A. Tayag; Edna G. Santiago; Minda A. Manado; Perla N. Alban; Dorothy Mae Agdamag; Suzette Lazo; Amelito Adel; Rosario Tactacan; Alicia O. Caspellan; Conrado Dayrit; Noel Espallardo (International Coconut Community, 2000)
The AIDS pandemic has caused global concern what with its threat to man’s survival and the enormous cost to prevent and treat the illness. No effective cure is possible but for the last fifteen years, countless studies were made to improve survival, delay disease progression or just improve the quality of life. Various clinical trials were designed to inhibit specific processes that are necessary for the human immunodeficiency virus (HIV) to survive the internal milieu. As important as these discoveries, are the precise methods of measuring the impact of these treatments. Only in the last five years has there been a better understanding of these processes and methods.